Atmospheric-pressure pulsed plasma actuators for flow control: shock wave and vortex characteristics. (29th May 2019) - Zhang, Cheng; Huang, Bangdou; Luo, Zhenbing; Che, Xueke; Yan, Ping; Shao, Tao
Abstract: Pulsed plasma actuators are used for an active flow control application since the 2000s. In this paper, we discuss shock wave and vortex characteristics in pulsed plasma actuators after an introduction of research progress on atmospheric-pressure discharge plasma actuators. First, the shock wave characteristics in surface dielectric barrier discharge (SDBD) actuator operating in diffuse-like and multi-streamer modes are discussed. In the most general case, a shock wave in a diffuse-like SDBD actuator is stronger and faster than in a multi-streamer SDBD actuator. Improved plasma actuators, such as the three-electrode SDBD actuator and the plasma synthetic jet actuator have the enhanced shock wave characteristics. Second, in order to investigate the effects of pulse parameters on the shock wave characteristics in nanosecond-pulse SDBD actuator, a particle image velocimetry system is used to capture the formation of starting vortexes at different pulse rise times, pulse durations, and pulse repetition frequencies (PRFs). It is shown that the velocity of a starting vortex significantly increases when the pulse rise time decreases from 400 ns to 50 ns due to a more significant hydrodynamic effect generated during a shorter rise time. This phenomenon is confirmed by calculating a reduced electric field E/N at a short rise time, which turns out to be higher at a shorter rise time than that at a relatively longer rise time. It is also shown that the velocity of a starting vortex increases and its active area enlarges when the PRF increases.